2010
DOI: 10.1242/jeb.043521
|View full text |Cite
|
Sign up to set email alerts
|

The shadow-induced withdrawal response, dermal photoreceptors, and their input to the higher-order interneuron RPeD11 in the pond snailLymnaea stagnalis

Abstract: SUMMARYThe shadow-induced withdrawal response in Lymnaea stagnalis is mediated by dermal photoreceptors located on the foot, mantle cavity, and skin around the pneumostome area. Here, we determined whether we could obtain a neural correlate of the withdrawal response elicited by a shadow in a higher-order central neuron that mediates withdrawal behavior. We measured the electrophysiological properties of the higher-order interneuron Right Pedal Dorsal 11 (RPeD11), which has a major role in Lymnaea withdrawal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Both food-finding and consummatory movements are modulated in response to different foods, in response to change in internal state, or as a result of previous learning as suggested by Sunada et al [28]. The tentacles and lip nervous contain the axon primary chemosensory neurons which sense food in environments [29].…”
Section: Discussionmentioning
confidence: 99%
“…Both food-finding and consummatory movements are modulated in response to different foods, in response to change in internal state, or as a result of previous learning as suggested by Sunada et al [28]. The tentacles and lip nervous contain the axon primary chemosensory neurons which sense food in environments [29].…”
Section: Discussionmentioning
confidence: 99%
“…Both McComb et al (2005) and Sunada et al (2010b) thought that juvenile Lymnaea perseverated because the memory for the task was occluded as a result of a lack of specific inhibitory circuits. This appears to be a recurring theme in the literature across species.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how this occurs. It is known that exposure to CE in juvenile Dutch snails counteracts the increased excitability of RPeD1 and forces the network into a more 'adult-like' configuration, thereby allowing operant conditioning to result in LTM formation (Sunada et al, 2010b;Forest et al, 2016). CE's effects in snails are blocked by DNA methylation blockers (Lukowiak et al, 2014) and the longlasting effects (at least 4 weeks) of training juvenile snails in CE are also dependent on DNA methylation (Forest et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As we recently found that five mRNA species belonging to the opsin family genes exist in L. valentianus (Matsuo et al, 2019), the expression of these mRNAs in the brain, the ST (including the eyes), the PS and the dorsal surface of the body (body wall, BW) was examined. We chose the PS because its light detection capability has been suggested in the pond snail Lymnaea stagnalis (Sunada et al, 2010). We detected all five mRNA species in the ST and three mRNA species in the brain (Opn5A, retinochrome and xenopsin; Fig.…”
Section: Expression Of Opsin Mrnamentioning
confidence: 99%